Species of the Genera Neopestalotiopsis and Alternaria as Dominant Pathogen Species Attacking Mastic Trees (Pistacia lentiscus var. Chia) - Nathalie N. Kamou; Stefanos Testempasis; Anastasia L. Lagopodi (Microbiology Research, 2023)
Between 2018 and 2021, several mastic trees (Pistacia lentiscus var. Chia) sampled in the field and the nursery of the Chios Mastiha Growers Association (CMGA) were analyzed to determine the cause of dominant diseases. Symptoms included defoliation, leaf, and twig blight, wilting and/or apoplexy of trees and apoplexy of young hardwood cuttings. Moreover, brown discoloration had also been observed on older woody parts of the trees such as branches and tree trunks. Several pathogens have been isolated and identified as the causing agents. Neopestalotiopsis and Alternaria species were isolated consistently from necrotic tissues of mastic trees (branches, twigs, and leaves) in the field and the nursery. All fungal isolates’ pathogenicity was confirmed by applying Koch’s postulates on young mastic trees under glasshouse conditions. Fungal pathogens were identified by sequence analyses of the ITS, β-tubulin, and histone gene regions. Alternaria species were analyzed further by sequencing the endopolygalacturonase (endoPG) and the Alternaria major allergen (Alta1) genes. More specifically, the isolates were identified as Neopestalotiopsis clavispora, Alternaria arborescens, and A. alternata based on morphological features and sequence analyses. This is the first report of N. clavispora, A. arborescens, and A. alternata on P. lentiscus var. Chia.